I vaccini per i minori tra salute pubblica e giustificazione di scelte individuali. Argomenti e riflessioni critiche su un tema controverso (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The issue of vaccines on minors is at the heart of the debate between society, law and science, in Italy as in other countries. This paper highlights some good reasons for vaccination practice, but also the main objections, misunderstandings and problems related to these topics. In this regard, we will propose a critical ethical-legal reflection, about the consideration of children’s vaccines as a fair practice.
Keywords: Vaccines; Health; Law; Ethics; Justice